Nguyễn Thị Ái Trang

Cứu

Nguyễn Hoàng Minh
16 tháng 9 2021 lúc 14:59

\(1,\\ ĐKXĐ:6-3x>0\Leftrightarrow-3x>-6\Leftrightarrow x< 2\)

\(2,A=\sqrt{5-2\sqrt{6}}-\sqrt{\left(\sqrt{2}-\sqrt{3}\right)^2}\\ A=\sqrt{\left(\sqrt{3}-\sqrt{2}\right)^2}-\left|\sqrt{2}-\sqrt{3}\right|\\ A=\left|\sqrt{3}-\sqrt{2}\right|-\left(\sqrt{3}-\sqrt{2}\right)\\ A=\sqrt{3}-\sqrt{2}-\sqrt{3}+\sqrt{2}=0\)

Bình luận (2)

Các câu hỏi tương tự
Nguyễn Đức Lâm
Xem chi tiết
Skem
Xem chi tiết
Horiii
Thuong Thuong
Thuong Thuong
Thuong Thuong
Huyền Trân
Nguyễn Tuấn Dũng
Dương tâm
Xem chi tiết